2015
DOI: 10.1111/jan.12708
|View full text |Cite
|
Sign up to set email alerts
|

Motivation is a crucial factor for adherence to a healthy lifestyle among people with coronary heart disease after percutaneous coronary intervention

Abstract: Patients who are motivated to perform self-care and consider the results of care to be important were more likely to adhere to a healthy lifestyle. Responsible patients were more likely to adhere to their medication. It is important to account for these elements as a part of secondary prevention strategies among patients with coronary heart disease after a percutaneous coronary intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 31 publications
8
73
0
6
Order By: Relevance
“…The important forms of health behaviour regarding the prevention of CHD—such as high‐to‐moderate physical activity and high vegetable consumption—predicted the motivation towards self‐care, sense of normality and perceived results of care, which were found to be crucial factors influencing adherence to treatment in many studies (Kääriäinen et al., ; Oikarinen, Engblom, & Kääriäinen, ; Kähkönen et al, ). The health benefits of physical activity are undeniably important when it comes to mitigating modifiable CHD risk factors, such as hypercholesterolaemia, hypertension, overweight and stress (Current Care Guideline: Stable Coronary Artery Disease, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The important forms of health behaviour regarding the prevention of CHD—such as high‐to‐moderate physical activity and high vegetable consumption—predicted the motivation towards self‐care, sense of normality and perceived results of care, which were found to be crucial factors influencing adherence to treatment in many studies (Kääriäinen et al., ; Oikarinen, Engblom, & Kääriäinen, ; Kähkönen et al, ). The health benefits of physical activity are undeniably important when it comes to mitigating modifiable CHD risk factors, such as hypercholesterolaemia, hypertension, overweight and stress (Current Care Guideline: Stable Coronary Artery Disease, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the dependent mean sum variables related to adherence to treatment were responsibility, cooperation, support from next of kin, sense of normality, motivation, results of care, support from nurses, support from physicians and fear of complications. (Kyngäs, ; Kyngäs, Duffy et al., ; Kyngäs, Skaar‐Chandler et al., ; Kääriäinen et al., ; Kähkönen et al, . )…”
Section: Methodsmentioning
confidence: 99%
“…Central here is the notion of 'adherence to treatment', or what used to be called compliance, and sometimes also known as 'concordance' depending on the emphasis being placed upon patient agency (Kähkönen, Kankkunen, Saaranen, Miettinen, Kyngäs & Lamidi, 2015). Motivation and responsibility figure highly as predictive factors in adherence, along with other items like feeling a sense of normality, fear of complications and support from family and health care professionals (ibid).…”
Section: Resultsmentioning
confidence: 99%
“…Kähkönen et al. () found that motivation was a key factor for adherence to secondary prevention. These findings highlight the need for patient participation during treatment to enhance the understanding of their condition and their motivation to initiate lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%